Certificateless Digital Signature Technology for e-Governance Solutions - Dhir, Shuchi; K.A, Dr. Sumithra Devi (Computer Science, 2019)
. In spite of the fact that digital signing is an essential requirement for implementation of e-governance solutions in any organization, its use in large scale Government ICT implementation is negligible in India. In order to understand the reasons for low-level acceptance of the technology, authors performed a detailed study of a famous e-governance initiative of India. The outcome of the study revealed that the reasons are related to the challenges concerning the use of cryptographic devices carrying private key and the complicated process of generation, maintenance and disposal of Digital Signature Certificates (DSC). The solution, for the challenges understood from the case study, required implementation of a certificateless technology where private keys should be generated as and when required rather than storing them on cryptographic devices. Although many solutions which provide certificateless technology exist, to date there have been no practical implementation for using biometrics for implementing the solution. This paper presents the first realistic architecture to implement Identity Based Cryptography with biometrics using RSA algorithm. The solution presented in the paper is capable of providing a certificateless digital signature technology to the users, where public and private keys are generated on-the-fly.